1987
DOI: 10.1113/jphysiol.1987.sp016450
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sodium‐calcium exchange current in single ventricular cells of guinea‐pig.

Abstract: 1. The Na-Ca exchange current was investigated in single ventricular cells from guinea-pig hearts by combining the techniques of whole-cell voltage clamp and intracellular perfusion. 2. The membrane conductance was minimized by blocking Ca and K channels as well as the Na-K pump. Under these conditions, when Ca2+ was loaded internally by a pipette solution containing 430 nM-Ca2+, changing the Li+-rich external solution to a Na+-rich one induced a significant inward current. Applying external Na+ in the absence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

51
435
4
1

Year Published

1989
1989
2002
2002

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 594 publications
(492 citation statements)
references
References 57 publications
51
435
4
1
Order By: Relevance
“…With regard to P. I. AARONSON AND C. D. BENHAM Ca2+ extrusion, however, similar (although wide) ranges of temperature dependence have been reported for the Na+-Ca2+ exchanger, and for the ATP-driven Ca2+ pump (e.g. Baker et al 1969;Larsen, Hinds & Vincenzi, 1978;Kimura et al 1987), so that the relative contributions of these two processes may not have been markedly perturbed. In spite of these potential drawbacks, however, the technique has proved useful for characterizing the properties of Na+{Ca2+ exchange in cardiac cells both when [Ca2+], was buffered (Kimura et al 1987) and when it was allowed to vary (Barcenas-Ruiz et al 1988).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…With regard to P. I. AARONSON AND C. D. BENHAM Ca2+ extrusion, however, similar (although wide) ranges of temperature dependence have been reported for the Na+-Ca2+ exchanger, and for the ATP-driven Ca2+ pump (e.g. Baker et al 1969;Larsen, Hinds & Vincenzi, 1978;Kimura et al 1987), so that the relative contributions of these two processes may not have been markedly perturbed. In spite of these potential drawbacks, however, the technique has proved useful for characterizing the properties of Na+{Ca2+ exchange in cardiac cells both when [Ca2+], was buffered (Kimura et al 1987) and when it was allowed to vary (Barcenas-Ruiz et al 1988).…”
Section: Discussionmentioning
confidence: 98%
“…Baker et al 1969;Larsen, Hinds & Vincenzi, 1978;Kimura et al 1987), so that the relative contributions of these two processes may not have been markedly perturbed. In spite of these potential drawbacks, however, the technique has proved useful for characterizing the properties of Na+{Ca2+ exchange in cardiac cells both when [Ca2+], was buffered (Kimura et al 1987) and when it was allowed to vary (Barcenas-Ruiz et al 1988). Ca2+ buffering has been compared in perfused cells and in ester-loaded cells using Fura-2, which has similar Ca2+-buffering properties to Indo-1; these studies (Gray, 1988) suggested that Ca2+ buffering was not seriously compromised by perfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Membrane depolarization would not affect a 2 : 1 exchange, but should decrease the driving force for Mg 2ϩ efflux through the exchange of either 3 : 1 or 4 : 1 stoichiometries with the reversal at positive potentials; it has been shown that the inward Na ϩ -Ca 2ϩ exchange current (influx of 3 Na ϩ and efflux of 1 Ca 2ϩ ) is inhibited by depolarization [29]. The observed acceleration of ⌬[Mg 2ϩ ] i by depolarization appears to be consistent with 1 : 1 (Na ϩ : Mg 2ϩ ) exchange.…”
mentioning
confidence: 99%